An investigation of GTN and NO related therapeutics in the treatment of acute stroke - Willmot, Mark (2007)
Background: High blood pressure is common in acute stroke and has been linked with poor outcome. Hence, outcome might be improved by lowering blood pressure. This thesis investigates the potential for glyceryl trinitrate, a nitric oxide donor, for lowering blood pressure in acute stroke. Methods: A systematic review was employed to clarify the relationship between outcome and BP in observational studies. Next two systematic reviews of animal studies using nitric oxide therapeutics in experimental stroke were performed to assess the effects on infarct volume and cerebral perfusion. Finally, two randomised controlled clinical trials of glyceryl trinitrate were performed in acute stroke patients to measure the systemic and cerebral haemodynamic effects. Results: In observational studies high blood pressure in acute stroke was associated with subsequent death, death or dependency, and death or deterioration. In experimental stroke nitric oxide sources and selective nitric oxide synthase inhibitors significantly reduced stroke volume. Glyceryl trinitrate lowered peripheral and central blood pressure and increased aortic compliance when given <48 hours from stroke. Glyceryl trinitrate did not alter quantitative measures of cerebral perfusion despite significantly lowering blood pressure <5 days from stroke. Conclusion: High blood pressure is a therapeutic target in acute stroke and animal data support the use of nitric oxide sources for lowering blood pressure. It is feasible to use glyceryl trinitrate for this purpose since it does not compromise cerebral perfusion. Trials now need to urgently assess the effect of lowering BP on outcome.